Fraksinasi Logam Pb dalam Sedimen Laut Untuk Estimasi Nilai Potensial Biovaibility di Kepulauan Wilayah Perairan Provinsi Maluku Utara - Inayah, Inayah; Samawi, M. Farid; Yaqin, Khusnul; Najamuddin, Najamuddin (Fakultas Ilmu Kelautan dan Perikanan (FIKP), Universitas Hasanuddin, 2023)
Determination of the geochemical fractionation of metals is also important to identify sources of metal pollutants in waters, whether they originate from natural processes or originate from human activities. This study aims to analyze the potential availability of Pb metal in sediments for biota and analyze the relationship between sediment grain size and total organic matter with the geochemical characteristics of Pb metal. The research was carried out in the North Maluku Waters Region in March 2023. consisting of 4 stations namely Ternate Island (Bastiong Harbor and Waters around Pertamina Jambula), Tidore (PLTU Waters) and Halmahera (Waters around the NHM Gold Mining area). And each station consists of 3 points. Sample testing was carried out at the Chemical Oceanography Laboratory, Faculty of Maritime Affairs and Fisheries, Hasanuddin University. And metal analysis was carried out at the Agency for Standardization and Industrial Services Policy Testing Laboratory BBSP JIHPMM Makassar City. Metal concentrations in the sediment fraction were determined by the BCR Sequential Extraction method (Based on Sarkar et al., (2014) The results showed that the total fraction was unstable at station 1, 2 and 3 were higher than the non-labile fraction, while at station 4 it was found that the total non-labile fraction was higher than the labile fraction.